2010
DOI: 10.1002/jhet.360
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some novel N‐alkyl/acyl/aroyl 2‐(chroman/6‐bromochroman‐2‐yl)‐1H‐benzimidazoles using ionic liquids and their antibacterial activity

Abstract: magnified image Synthesis of some novel N‐substituted 2‐(chroman/6‐bromochroman‐2‐yl)‐1H‐benzimidazoles by the condensation of 3,4‐dihydro‐2H‐chroman‐2‐carboxylic acid and 6‐bromo‐3,4‐dihydro‐2H‐chroman‐2‐carboxylic acid with o‐phenylenediamine in ionic liquid (IL) [bmim]BF4 and subsequent reactions at the benzimidazole‐NH with different types of electrophiles in ILs [bmim]BF4 = 1‐butyl‐3‐methylimidazolium tetrafluoroborate, [bmim]PF6 = 1‐butyl‐3‐methylimidazolium hexafluorophosphate and [buPy]BF4 = butylpyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…m. p. 219°C. 1 The procedure was similar to the synthesis phenylendiamine 1. Pd(OAc) 2 (0.25 g, 1.12 mmol); tBu 3 P (0.68 g, 3.37 mmol); 1,2-dibromo-benzene (6.6 g, 28 mmol); 2,6-diisopropylaniline (9.90 g, 56 mmol); NaOtBu (8.06 g, 84 mmol).…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…m. p. 219°C. 1 The procedure was similar to the synthesis phenylendiamine 1. Pd(OAc) 2 (0.25 g, 1.12 mmol); tBu 3 P (0.68 g, 3.37 mmol); 1,2-dibromo-benzene (6.6 g, 28 mmol); 2,6-diisopropylaniline (9.90 g, 56 mmol); NaOtBu (8.06 g, 84 mmol).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…In order to carry out a structural modification on phenylene diamines, Harlan et al reported a simple catalyzed coupling reaction to isolated N,N-diaryl-o-phenylenediamine derivatives [15]. Base on that, in this paper, we describe the molecular structure and their biological activity of a short series of N,N 0 -aryl-o-phenylenediamines (Scheme 2) such as N,N 0 -2,6-dimethylphenyl-o-phenylenediamine (1), N,N 0 -2,4,6-trimethylphenyl-o-phenylenediamine (2), and N,N 0 -2,6-diisopropylphenyl-o-phenylenediamine (3).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation